Super 30 : changing the world 30 students at a time, Anand Kumar - Mathew, Biju (Gurgaon Penguin Group, 2016)
"Revolutionary experiment to bring about social change" through success in Indian math exam IIT JEE.
Include Colour Illustration
Keywords: Kumar, Anand, -- 1973 -- Education -- India -- History -- Teachers -- India -- Biography